THE COMMUNICATION MODEL OF STUDENT-BASED ISLAMIC BOARDING SCHOOLS IN PRESERVING MORAL VALUES IN JEMBER REGENCY - Robiatul Adawiyah (Indonesian Journal of Islamic Communication, 2022)
Student-based Islamic boarding schools (pesantren mahasiswa) have a unique communication model in preserving moral values, which can be analyzed using Lasswell's communication model. Al-Husna Islamic Boarding School in Jember is one such pesantren mahasiswa that accommodates a significant number of students from various universities in the Jember area. This qualitative research, using a phenomenological approach, reveals that the communication model employed by the pesantren to maintain moral values is implemented through specific rules and routine activities within the boarding school. These include the practice of five daily congregational prayers, the study of classical Islamic texts (kitab kuning) after dawn prayer, diniyah classes, mandatory permission before leaving the boarding school, compliance with the pesantren dress code, and the commemoration of Islamic holidays (PHBI). However, there are several challenges in maintaining this communication model. The increasing number of students has led to reduced effectiveness of the implemented rules and activities. Additionally, the students’ busy academic lives outside the pesantren, the feelings of boredom among senior students leading to a lack of enthusiasm in participating in activities, and the adaptation difficulties experienced by new students all contribute to the obstacles in upholding the pesantren’s moral standards.